2020
DOI: 10.3727/096504019x15668125347026
|View full text |Cite
|
Sign up to set email alerts
|

PRKAA1 Promotes Proliferation and Inhibits Apoptosis of Gastric Cancer Cells Through Activating JNK1 and Akt Pathways

Abstract: PRKAA1 (protein kinase AMP-activated catalytic subunit α 1) is a catalytic subunit of AMP-activated protein kinase (AMPK), which plays a key role in regulating cellular energy metabolism through phosphorylation, and genetic variations in the PRKAA1 have been found to be associated with gastric cancer risk. However, the effect and underlying molecular mechanism of PRKAA1 on gastric cancer tumorigenesis, especially the proliferation and apoptosis, are not fully understood. Our data showed that PRKAA1 is highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Conversely, the overexpression of PCSK9 in MGC-803 cells facilitated MAPK signaling pathway, accelerating the migration/invasion of the cells when compared with the controls. Previous studies have shown that MAPK signaling pathway plays a central role in the stimulation of cancer cell proliferation, apoptosis, and metastasis (35)(36)(37). And also p38 MAPK participates in resistance to chemotherapy drugs like cisplatin, irinotecan, and 5-fluorouracil (38), which are often administered in GC chemotherapy regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the overexpression of PCSK9 in MGC-803 cells facilitated MAPK signaling pathway, accelerating the migration/invasion of the cells when compared with the controls. Previous studies have shown that MAPK signaling pathway plays a central role in the stimulation of cancer cell proliferation, apoptosis, and metastasis (35)(36)(37). And also p38 MAPK participates in resistance to chemotherapy drugs like cisplatin, irinotecan, and 5-fluorouracil (38), which are often administered in GC chemotherapy regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic alteration, expression, and activity of AKT1, MAPK1, and MAPK3 can also affect the risk of developing GC, clinical outcomes, recurrence, and survival rates in patients [67][68][69] . Additionally, c-Jun NH2-terminal kinase 1 (JNK1; encoded by MAPK8), a kinase that coordinates cell migration, apoptosis, survival, and proliferation, plays an important role in the carcinogenesis and development of GC [70][71][72][73] . Furthermore, genetic mutations in PI3KCA is a determinant of the chemosensitivity of GC 74 .…”
Section: Discussionmentioning
confidence: 99%
“…As a cell energy sensor, it regulates intracellular nutrition and energy levels via glucose and lipid metabolic pathways [57]. Studies have recently reported that PRKAA1 modulates GC cell proliferation via the regulation of the c-JNK, AKT, and NF-κB signaling pathways [58,59]. Protein-protein interactions are the cornerstone of numerous biological functions.…”
Section: Discussionmentioning
confidence: 99%